Improved design of peptides exhibiting angiogenic activities for clinical applications. Issue 19 (1st October 2020) - Tominaga, Yuki; Kitagawa, Atsushi; Nokihara, Kiyoshi
Graphical abstract: Abstract: Vascularization is one of the key steps for engraftment in regenerative medicine. Previously one of the authors had discovered peptides exhibiting significant angiogenic activities designated AGP and elucidated the active core. For neovascularization basic fibroblast growth factor is used although permeation can be envisaged. The original AGPs did not suffer from this although their half-life times are short because of decomposition by endogenous enzymes. Several new AGP-libraries have been constructed and their enzymatic resistance has been investigated by the use of human umbilical vein endothelial cells to find candidates for clinical applications.